Penyimpangan Penafsir dari Zaman Klasik Hingga Zaman Now (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2018)
In some commentaries of classical and modern, with a variety of systems and methods of each of the orientation and understanding there are many texts diverge in understanding the texts of the Qur’an. Irregularities also occur within the meaning takwil that does not comply with the correct Arabic feeling and also eliminates the correct of the Al Quran itself, even contrary to the basic teachings of Islam, so that readers can plunge to disbelief. Deviations were found in the book of commentary from time to time in various schools and sects. This scientific article will describe some of the irregularities that occurred in the interpretation.